Estrutura societária e controle minoritário na Brasil Telecom: análise do poder exercido pelo Opportunity de 2003 a 2005 - Belline, Alexandra Cisotto (2016)
Since the mid-1990s the Brazilian business environment has experienced a significant increase in the sophistication of modeling corporate structures for large enterprises, a type of knowledge, however, mostly restricted to participants in these ventures and its legal and financial counsel. In the case of the corporate structure of Brazil Telecom, however, it was possible to access all documents and information in order to study this structure, due to the massive litigation involving this company for almost ten years , where most part of the documents analyzed in this dissertation were found. This material is precious because the case of Brazil Telecom - known as one of the major in Brazilian corporate law - has a very important peculiarity: the group was managed by a minority shareholder, Opportunity group, which exercised power control during those ten years, despite its diminished equity interest and strong opposition suffered from major shareholders for most of the time in which that power was exercised. The aim of this study is to reveal the legal techniques that allowed the exercise of this power, as well as to seek to understand why, in spite of so much opposition from other shareholders and the massive litigation, it took years for the Opportunity to be definitely removed from the administration and the exercise of controlling power of Brazil Telecom.